BUGGED MOBILE PHONES OF HEALTH CARE PROVIDERS COULD TRANSMIT MORE THAN JUST A CALL: Bugged Mobile Phones - Saeed, Muhammad; Naveed, Muhammad; Rasheed, Farhan; Iram, Shagufta; Akhtar, Mehwish; Imran, Ambreen Anwar (Pakistan Armed Forces Medical Journal, 2018)
Objective: To evaluate contamination of mobile phones from healthcare workers with nosocomial pathogens. Study Design: Cross sectional study. Place and Duration of Study: Microbiology Section, Pathology Department, Allama Iqbal Medical College, Jinnah Hospital Lahore, from Jul 2016 to Feb 2017. Material and Methods: A total of 257 culture swabs were collected from the mobile phones of HCWs of Jinnah Hospital, Lahore, every samples was processed for bacterial culture following standard protocols. Organisms were identified by colonial morphology, gram staining, and with the help of API 20NE and API 20E. Results: Out of 257 mobile phones, 66% (n=169) were contaminated with any 01/>01 bacteria. Most prominent pathogen isolated was coagulase negative staphyloccoi (CoNS) followed by Staphylococcus aureus 34.8% and 24% respectively. Other microorganisms identified, were Acinetobacter species (12.6%) n=29, Bacillus species 10.4% (n=24), Enterococcus species 4.8% (n=11), Escherichia coli 3.5% (n=8), Micrococcus species 3.5% (n=8), Diphtheroids 2.5% (n=5) Klebsiella species 1.7% (n=4), Aspergillus species 1.7% (n=4) and Pseudomonas aeruginosa 1.0% (n=2.0). Out of 55 Staphylococcus aureus, Methicillin-resistant Staphylococcus aureus (MRSA) were 36.0% (n=20) and methicillin-sensitive Staphylococcus aureus (MSSA) were 64.0% (n=35). Conclusion: In the hospital setting mobile phones should be regularly decontaminated. Moreover, utmost emphasis needs to be paid to hand washing practices among HCWs.